Separation of flavonoids from Millettia griffithii with high‐performance counter‐current chromatography guided by anti‐inflammatory activity. Issue 3 (28th December 2014) - Tang, Huan; Wu, Bo; Chen, Kai; Pei, Heying; Wu, Wenshuang; Ma, Liang; Peng, Aihua; Ye, Haoyu; Chen, Lijuan
<x xml:space="preserve">Abstract</x> Millettia griffithii is a unique Chinese plant located in the southern part of Yunnan Province. Up to now, there is no report about its phytochemical or related bioactivity research. In our previous study, the n‐hexane crude extract of Millettia griffithii revealed significant anti‐inflammatory activity at 100 μg/mL, inspiring us to explore the anti‐inflammatory constituents. Four fractions (I, II, III, and A) were fractionated from n‐hexane crude extract by high‐performance counter‐current chromatography with solvent system composed of n‐hexane/ethyl acetate/methanol/water (8:9:8:9, v/v) and then were investigated for the potent anti‐inflammatory activity. Fraction A, with the most potent inhibitory activity was further separated to give another four fractions (IV, V, VI, and B) with solvent system composed of n‐hexane/ethyl acetate/methanol/water (8:4:8:4, v/v). Compound V and fraction B exhibited remarkable anti‐inflammatory activity with nitric oxide inhibitory rate of 80 and 65%, which was worth further fractionation. Then, three fractions (VII, VIII, and IX) were separated from fraction B with a solvent system composed of n‐hexane/ethyl acetate/methanol/water (8:1:8:1, v/v), with compound VIII demonstrating the most potent inhibitory activity (80%). Finally, the IC50 values of compound V and VIII were tested as 38.2 and 14.9 μM. The structures were identified by electrospray ionization mass spectrometry and1H and 13C NMR spectroscopy.